2016
DOI: 10.1186/s11689-016-9175-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations between social cognition, skills, and function and subclinical negative and positive symptoms in 22q11.2 deletion syndrome

Abstract: BackgroundIdentification of the early signs of schizophrenia would be a major achievement for the early intervention and prevention strategies in psychiatry. Social impairments are defining features of schizophrenia. Impairments of individual layers of social competencies are frequently described in individuals with 22q11.2 deletion syndrome (22q11.2DS), who have high risk of schizophrenia. It is unclear whether and to what extent social impairments associate with subclinical negative and positive symptoms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
41
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 70 publications
(79 reference statements)
7
41
1
Order By: Relevance
“…One study on 22q11DS found a signi cant inverse association, indicating poorer performance on a ToM task (anthropomorphic animations) was associated with higher SRS scores (20). Speci c to the relationship between TASIT and SRS, a prior study did not nd a signi cant association between TASIT performance and SRS in 22q11DS (48) in line with our ndings. One study on adult CHR participants found a signi cant association between higher TASIT scores and lower self-reported SRS scores (50).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…One study on 22q11DS found a signi cant inverse association, indicating poorer performance on a ToM task (anthropomorphic animations) was associated with higher SRS scores (20). Speci c to the relationship between TASIT and SRS, a prior study did not nd a signi cant association between TASIT performance and SRS in 22q11DS (48) in line with our ndings. One study on adult CHR participants found a signi cant association between higher TASIT scores and lower self-reported SRS scores (50).…”
Section: Discussionsupporting
confidence: 89%
“…Despite this, we did not nd a signi cant relationship between social cognition performance and real-world social behavior for any clinical group, although the ndings were trending in the expected direction across all groups. While numerous studies have used ToM tasks and the SRS concurrently in order to broadly examine social outcomes in our speci ed clinical groups, few have directly assessed the relationship between the two types of measures (20,48,82). A recent study in ASD adolescents found that combined poor performance on several social cognition tasks (ToM tasks, emotion-recognition tasks, and anthropomorphic animations) was collectively associated with elevated SRS scores (83).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It includes a wide range of skills such as difficulty identifying emotions, feeling connected to others, inferring people's thoughts, and reacting emotionally to others (Green, Horan, & Lee, 2015). Dysfunctional social cognition in schizophrenia and in 22q11.2DS is now well established and supported by replicated studies (Campbell et al, 2015;Green et al, 2005Green et al, , 2008Penn et al, 2008;Savla et al, 2013;Vangkilde et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In SCZ and 22q11.2DS, dysfunctional social cognition is now well established and attested by significant and consistent scientific body of literature (Campbell, McCabe, Melville, Strutt, & Schall, 2015;Green et al, 2008;Green, Olivier, Crawley, Penn, & Silverstein, 2005;Penn, Sanna, & Roberts, 2008;Savla, Vella, Armstrong, Penn, & Twamley, 2013;Vangkilde et al, 2016). Emotional processing has been widely studied, and deficits in facial and vocal emotion recognition are now well established (Chan, Li, Cheung, & Gong, 2010;Irani, Seligman, Kamath, Kohler, & Gur, 2012;Leleu et al, 2016;McCabe et al, 2016).…”
mentioning
confidence: 96%